Thatcherism and its influences on the british economy from 1979 to 1990 = Chủ nghĩa Thatcher và sự ảnh hưởng của nó tới nền kinh tế nước Anh giai đoạn 1979 đến 1990 - Nguyễn, Vũ Hồng Anh (2020)
The unique Margaret Thatcher is one of the most outstanding politicians of the twentieth century. Her set of ideas, often named Thatcherism, played an important part in the British history, especially in the economy. Hardly ever before, could a politician reverse the situation of an economic crisis as spectacularly as she did. This legend is the inspiration for the study: Thatcherism and its influences on the British economy during her term as the Prime Minister. It aims at answering two questions: What is Thatcherism? and How did it influence the British economy from 1979 to 1990? A qualitative research was conducted in order to figure out reliable answers. Related documents were collected and then analyzed as well as compared and contrasted so that the most trustworthy information and the best arguments were synthesized and presented in the research. The study defines Thatcherism as a series of political ideas and attitudes rather than an ideology based on the differences in comparison with socialism or capitalism. It also points out the features of Thatcherism which were anti-socialism and individualism. When it comes to influences, the research indicates that there were three achievements that Thatcherism acquired in the period of 1979 – 1900. They were inflation reduction, privatization and the trade unions’ power restriction. These achievements rescued the declining economy of Britain and brought it a new life. In addition, the side-effects of Thatcherism such as the high unemployment rate, the rise of private monopoly, or inequality are also included in the research to provide a profound outlook on this controversial issue